The onset of the volcanism in the Ciomadul Volcanic Dome Complex (Eastern Carpathians): eruption chronology and magma type variation - Molnár, Kata; Schmitt, Axel Karl (Journal of volcanology and geothermal research, 2018)
Combined zircon U-Th-Pb and (U-Th)/He dating was applied to refine the eruption chronology of the last 2Myr for the andesitic and dacitic Pilişca volcano and Ciomadul Volcanic Dome Complex (CVDC), the youngest volcanic area of the Carpathian-Pannonian region, located in the southernmost Harghita, eastern-central Europe. The proposed eruption ages, which are supported also by the youngest zircon crystallization ages, are much younger than the previously determined K/Ar ages. By dating every known eruption center in the CVDC, repose times between eruptive events were also accurately determined. Eruption of the andesite at Murgul Mare (1865±87ka) and dacite of the Pilişca volcanic complex (1640±37ka) terminated an earlier pulse of volcanic activity within the southernmost Harghita region, west of the Olt valley. This was followed by the onset of the volcanism in the CVDC, which occurred after several 100skyr of eruptive quiescence. At ca. 1Ma a significant change in the composition of erupted magma occurred from medium-K calc-alkaline compositions to high-K dacitic (Baba-Laposa dome at 942±65ka) and shoshonitic magmas (Malnaş and Bixad domes; 964±46ka and 907±66ka, respectively). Noteworthy, eruptions of magmas with distinct chemical compositions occurred within a restricted area, a few km from one another. These oldest lava domes of the CVDC form a NNE-SSW striking tectonic lineament along the Olt valley. Following a brief (ca. 100kyr) hiatus, extrusion of high-K andesitic magma continued at Dealul Mare (842±53ka). After another ca. 200kyr period of quiescence two high-K dacitic lava domes extruded (Puturosul: 642±44ka and Balvanyos: 583±30ka). The Turnul Apor lava extrusion occurred after a ca. 200kyr repose time (at 344±33ka), whereas formation of the Haramul Mic lava dome (154±16ka) represents the onset of the development of the prominent Ciomadul volcano. The accurate determination of eruption dates shows that the volcanic eruptions were often separated by prolonged (ca. 100 to 200kyr) quiescence periods. Demonstration of recurrence of volcanism even after such long dormancy has to be considered in assessing volcanic hazards, particularly in seemingly inactive volcanic areas, where no Holocene eruptions occurred. The term of ‘volcanoes with Potentially Active Magma Storage’ illustrates the potential of volcanic rejuvenation for such long-dormant volcanoes with the existence of melt-bearing crustal magma body.